Fine and hyperfine excitation of CCN by He. Issue 2 (13th July 2020) - Chefai, A; Jaidane, N E; Hammami, K; Lique, F
ABSTRACT: The relative abundance of cyanide and isocyanide molecules is a sensitive tracer of the physical conditions in the interstellar and circumstellar media. Accurate modelling of collisional and radiative processes implying these species opens the way for accurate estimation of their abundances. The present paper focuses on the computation of collisional rate coefficients for fine and hyperfine (de-)excitation of the CCN molecule (one of the C2 N isomers) in collision with He, for temperatures up to 150 K. Using a time independent coupled-channel approach, scattering calculations were performed for transitions implying the lowest 56 fine structure levels and the corresponding 166 hyperfine structure levels belonging to both 2 Π1/2 and 2 Π3/2 spin-orbit manifolds. We provided, for the first time, realistic collisional data for the CCN radical. Propensity rules for fine and hyperfine transitions are discussed. As a first application, we evaluated the impact of these new data on the astrophysical modelling through radiative transfer calculations. We obtained the brightness and excitation temperatures of selected lines observed towards circumstellar envelopes and we found that local thermodynamic equilibrium conditions are not fulfilled for this species. As a consequence, our results indicate that the abundance of the CCN derived from the observations has to be revised since the observation modelling strongly depends on the collisional data used.